2012
DOI: 10.1016/j.conbuildmat.2011.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Mix design considerations for warm mix recycled asphalt with bitumen emulsion

Abstract: a b s t r a c tWarm mix recycled asphalt with bitumen emulsion is a technique still in development, which has proved to be very promising, both in economic and environmental terms.This technology allows recycling at a lower temperature, increases the amount of recycled materials and thus, saves energy and reduces CO 2 emissions. It allows to leverage existing raw materials on the degraded pavement and to reduce energy costs in the manufacture of the new mixture. The laboratory study was conducted to analyse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Increase in RAP proportion increases the resistance to moisture damage [57,60]. The warm mixes produced using RAP showed the value of TSR above the minimum required 80%, indicating good resistance towards moisture damage of these mixes [71]. The WMA additive does not impart any detrimental impact on the water sensitivity of WMA mix materials [54].…”
Section: Moisture Susceptibilitymentioning
confidence: 95%
“…Increase in RAP proportion increases the resistance to moisture damage [57,60]. The warm mixes produced using RAP showed the value of TSR above the minimum required 80%, indicating good resistance towards moisture damage of these mixes [71]. The WMA additive does not impart any detrimental impact on the water sensitivity of WMA mix materials [54].…”
Section: Moisture Susceptibilitymentioning
confidence: 95%
“…18 In Europe, more than 50 million tonnes of asphalt pavement material is recycled in-place every year. 19 It is verified that about 95% of asphalt mixture produced and reused is up to 50% RAP. 19 Higher RAP percentage in mixes is possible because of decreasing viscosity of the stiff binder in RAP.…”
Section: Environmental and Economical Prospectivementioning
confidence: 97%
“…19 It is verified that about 95% of asphalt mixture produced and reused is up to 50% RAP. 19 Higher RAP percentage in mixes is possible because of decreasing viscosity of the stiff binder in RAP. 14 Prowell et al 11 and Aqua 15 black solution guidelines reported that lower temperatures mean the possibility of running < producing?…”
Section: Environmental and Economical Prospectivementioning
confidence: 97%
“…The environmental concern is an argument commonly used by several entities in order to stimulate both the use of warm mix asphalt and of warm mix asphalt with RAP incorporation, that is why studies have been conducted to verify the performance of these mixtures Dinis-Almeida et al, 2012a, 2012bGuo et al, 2014;Miliutenko et al, 2013;Sengoz and Oylumluoglu, 2013;Silva et al, 2012;Sun et al, 2014;Tatari et al, 2012;Vidal et al, 2013). These studies have led to the conclusion that the fatigue is the cause of the cracking of bituminous pavements, because it represents the ability this material has to respond to the repeated application of loads from traffic, to certain environmental and speed conditions (Teixeira, 2000).…”
Section: Introductionmentioning
confidence: 99%